Efeitos de um programa de reabilitação cardíaca nas variáveis independentes do esforço máximo em pacientes com insuficiência cardíaca crônica - Silveira, Amanda Soares Felismino (2020)
Introduction: The effects of Cardiac Rehabilitation (CR) in patients with chronic heart failure (HF) are evaluated during maximal exercise and are mainly translated by changes in oxygen uptake at peak effort (VO2peak). However, in severely limited patients, this measure may be compromised by the inability to sustain maximum loads of physical exercise. Thus, other variables, since they are employed independently of the maximum effort, have been studied such as the Anaerobic Limit - LA, relationship between minute ventilation and carbon dioxide production -VE / VCO2Slope, ventilatory efficiency - OUES and ventilatory oscillation - OV . In addition, the use of these variables analyzed together can provide important clinical elements on stratification of prognostic risk and cardiac event. Objective: To evaluate the effects of Cardiac Rehabilitation (CR) on the independent variables of maximum effort (LA, VE / VCO2slope, OUES and OV) and on risk stratification in patients with chronic HF, as well as to evaluate whether and how OUES and VO2LA are correlate with the aerobic capacity of patients with chronic HF and determine which parameters are associated with VO2LA and OUES in patients with chronic HF. Materials and Method: This is a series of cases with patients with compensated chronic HF. Clinical, spirometric and physical stress test assessments (ergometry and/or ergospirometry) were performed before the CR program. Then, the patients referred to the CR program that included a dose of 36h / patient of clinical exercises, individualized (aerobic and resistance) and supervised, 3 times/week for 12 weeks, with weekly load readjustment, being reassessed as for the exercise test. physical effort after the 12- week CR period. Results and discussion: 45 patients with chronic HF with an average age of 49.8 ± 12.97 years and an Ejection Fraction (EF) of 39.0 ± 15.8% were evaluated. An increase of 124 seconds (p <0.001) was identified in the average of the total test time and 24.1% in the workload in the pre and post-CR comparison. Regarding the metabolic analysis, we had an increase of 18.3% in VO2peak after CR, as well as an increase of 12.9% VO2 at the time of LA and 20.14% in OUES75%, in addition to a reduction in the mean VE/VCO2Slope and the presence of OV, which improved the risk stratification of 4 patients. It was also possible to conclude that OUES is able to identify patients with chronic HF with different aerobic capacities (<or> 70% predicted VO2) such as LA (ASC = 0.865, p = <0.0001; ASC = 0.800, p = 0.002, respectively), and there is no significant difference in the comparison between the receiver operating characteristic (ROC) curves. The regression analysis identified cardiovascular and pulmonary factors (EF, diastolic diameter and volume, forced vital capacity and maximum voluntary ventilation) related to both variables. Conclusion: It is concluded that the independent variables of maximum effort are able to identify the effects of CR with an individualized dose of exercise and readjusted weekly as well as those dependent on maximum effort. And that the variables OUES75% and VO2LA correlate with aerobic capacity and are effective in differentiating patients with chronic HF from their aerobic capacity. In addition, the measurements are associated with cardiovascular and pulmonary parameters.